Impacts of stocking density rates on welfare, growth, and hemato-biochemical profile in broiler chickens - Zabir, Mishkatul; Miah, Mohammad Alam; Alam, Mahabub; Bhuiyan, Md Eftakhar Jahan; Haque, Md Iqramul; Sujan, Khaled Mahmud; Mustari, Afrina (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: The study investigated the effect of different stocking density (SD) rates on the welfare, growth, and hemato-biochemical parameters in broiler chickens. Materials and Methods: 106 broiler chicks of 10 days old were used and assigned into four groups: A, B, C, and D. The chicks of group A were reared in floor space containing one bird per square foot area (SD1.0). The chicks of groups B, C, and D were reared at 1.5, 2.0, and 2.5 birds per square foot area (SD1.5, SD2.0, and SD2.5). Welfare, body weight, and hemato-biochemical parameters were assessed and monitored by physical observation and laboratory methods. Results: The birds reared at SD2.0, and SD2.5 rates showed increased panting breathing. Wet feces adhered below the vent. There were a significant number of birds showing dirtiness of body and feathers. Birds reared in SD2.5 were familiar with moist litters and high ammonia smell. Foot-pad dermatitis, scratches, and blister formation were detected in the leg. The study revealed that the higher SD negatively correlated to the welfare behavior indicators. Live body weight was significantly (p < 0.05) decreased in birds reared at higher SD rates. Birds housed in SD1.0 and SD1.5 are optimum for body weight and improved feed conversion ratio. The hemato-biochemical parameters of birds reared at various SD rates did not differ. The total leucocyte count increased significantly, while total serum proteins decreased gradually as SD rates increased. Conclusion: This work explores that higher SD negatively affects welfare and growth performance in broiler chickens. J. Adv. Vet. Anim. Res., 8(4): 642–649, December 2021 http://doi.org/10.5455/javar.2021.h556